Quasi-linearly polarized hybrid modes in tapered and metal-coated tips with circular apertures: understanding the functionality of aperture tips. (20th June 2017) - Tugchin, B N; Janunts, N; Steinert, M; Dietrich, K; Kley, E B; Tünnermann, A; Pertsch, T
Abstract: In this study, we investigate analytically and experimentally the roles of quasi-linearly polarized (LP), hybrid, plasmonic and photonic modes in optical detection and excitation with aperture tips in scanning near-field optical microscopy. Aperture tips are tapered and metal-coated optical fibers where small circular apertures are made at the apex. In aperture tips, there exist plasmonic modes that are bound at the interface of the metal cladding to the inner dielectric fiber and photonic modes that are guided in the area of the increased index in the dielectric fiber core. The fundamental photonic mode, although excited by the free-space Gaussian beam, experiences cutoff and turns into an evanescent mode. The photonic mode also becomes lossier than the plasmonic mode toward the tip aperture, and its power decay due to absorption and reflection is expected to be at least 10 −9 . In contrast, the fundamental plasmonic mode has no cutoff and thus reaches all the way to the tip aperture. Due to the non-adiabaticity of both modes' propagations through the taper below a core radius of 600 nm, there occurs coupling between the modes. The transmission efficiency of the plasmonic mode, including the coupling efficiency and the propagation loss, is expected to be about 10 −6 that is at least 3 orders of magnitude larger than that of the photonic mode. Toward the tip aperture, the longitudinal field of the photonic mode becomes stronger than the transverse ones while the transverse fields always dominate for the plasmonic mode. Experimentally, we obtain polarization resolved images of the near-field at the tip aperture and compare with the x - and y -components of the fundamental quasi-LP plasmonic and photonic modes. The results show that not only the pattern but also the intensity ratios of the x - and y -components of the aperture near-field match with that of the fundamental plasmonic mode. Consequently, we conclude that only the plasmonic mode reaches the tip aperture and thus governs the near-field interaction outside the tip aperture. Our conclusion remains valid for all aperture tips regardless of the cladding metal type that mainly influences the total transmission efficiency of the aperture tip.